(untitled) (Acta Scientiarum. Biological Sciences, 2024)
According to the International Union for Conservation of Nature [IUCN], Melocactus conoideus Buin. & Bred is a critically endangered cactus species, and genetic studies are still needed to support conservation strategies. Thus, this study aimed to characterize the genetic diversity and structure of M. conoideus using Inter Simple Sequence Repeats (ISSR) markers. We amplified the genomic DNA of 126 M. conoideus genotypes from the municipality of Vitória da Conquista, state of Bahia (Brazil), obtained within and outside the limits of the M. conoideus Environmental Reserve. To this end, 13 ISSR primers were used, and the genetic amplification profile was subjected to statistical analysis of genetic diversity and structure. One hundred and ninety-one markers were analyzed, 188 of which (97.7%) were polymorphic. Moderate genetic diversity (h = 0.29) was observed, with a significant variation when considering protected and unprotected regions. The set of markers varied between informative and uninformative (mean PIC = 0.24), and genetic differentiation ranged from moderate to high (Gst = 0.32) between populations inside and outside the environmental reserve. Gene flow between populations (Nm) was estimated at 1.02. Analysis of molecular variance revealed 33% of genetic variation between populations and 67% within populations. Bayesian analysis and principal coordinate analysis (PCoA) confirmed the existence of two groups (K=2), with individuals from the reserve showing homogeneity for a single gene pool. This result highlights the influence of exclusive genomic regions on the genetic structure of the species. These results suggest that the auto-ecology of M. conoideus influences variability and differentiation levels, besides contributing to genetic structuring in subpopulations. Our findings may help in genetic conservation and management planning, as well as in the in situ demographic expansion used by the bodies responsible for M. conoideus population maintenance.